Pengembangan Skala Eco Stress Index (ESI) dalam Mendeteksi Stress Lingkungan Generasi Muda - Siti Fadila Utiarahman; Nazwa Nurfani Putri; Reinalisa Paputungan; Jhosua Manuel Solang Ottay; Mohammad Rizki B. Dunggio (Lembaga Penelitian, Universitas Warmadewa, 2026)
Global environmental issues such as climate change and the ecological crisis are increasingly affecting the psychological well-being of young people who are highly exposed to environmental information. Previous studies on ecological anxiety have largely focused on emotional anxiety responses, while the broader psychological distress caused by the environmental crisis remains underexplored. Therefore, this study aims to develop the Ecological Stress Index (ESI) as an instrument to measure ecological stress among young adults. This study used a quantitative approach with a cross-sectional design involving 214 participants aged 17–25 years selected through purposive sampling. This instrument was developed based on four dimensions: emotional distress, cognitive rumination and worry, existential threat, and functional impact and behavioral responses. Data were analyzed using Exploratory Factor Analysis (EFA) and Confirmatory Factor Analysis (CFA). The reliability test of the eco-stress index produced a reliability coefficient value of ? = 0.940, indicating that the Eco-Stress Index scale demonstrates high reliability in measuring environmental stress among young people in Indonesia. The results of the study show that the Eco Stress Index (ESI) has good construct validity and can be used to identify environmental stress among the younger generation.